2019
DOI: 10.1021/acs.est.8b06510
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Greenhouse Gas Mitigation Potential of Harvested Wood Products Substitution in China

Abstract: Substituting harvested wood products (HWP) for greenhouse gas (GHG) intensive nonwood materials in long-lived end uses has the potential to significantly reduce GHG emissions. To determine the mitigation effects of HWP substitution, we produced China-specific wood displacement factors (DFs) by HWP end use subcategory, defined as tonnes of carbon (tC) of reduced emissions per tC contained by the HWP substituted for typical alternative nonwood materials. The weighted average DFs for substituting HWP for nonwood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…Secondly, in assessing the climate change mitigation potential of forest growth and wood use at a regional, national or global scale, a current practice is to apply averaged displacement factors to large segments of the HWP production [27][28][29][30][31][32] . Most studies using this approach conclude that GHG benefits from substitution globally surpass those which would result from the growth of existing forests, thus inciting to increase harvesting.…”
Section: Openmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, in assessing the climate change mitigation potential of forest growth and wood use at a regional, national or global scale, a current practice is to apply averaged displacement factors to large segments of the HWP production [27][28][29][30][31][32] . Most studies using this approach conclude that GHG benefits from substitution globally surpass those which would result from the growth of existing forests, thus inciting to increase harvesting.…”
Section: Openmentioning
confidence: 99%
“…For instance, Sathre and O'Connor 9 report displacement factors ranging from −2.3 to 15 tons of carbon emission reduction per ton of carbon in wood products, depending on specific applications in building construction, with an unweighted average value of 2.1 tC/tC. Many authors put forward comparable weighted estimates with slight differences owing to the country and application sector concerned [27][28][29][30][31][32] . However, as evidenced by Fig.…”
Section: Carbon Footprint Of Wood Utilization As a Materialmentioning
confidence: 99%
“…Many authors put forward comparable estimates with slight differences owing to the country and application sector concerned. Examples are weighted averages of 3.48 tC/tC and 1.36 tC/tC, respectively, for construction and furniture production in China [24]; 1.5 tC/tC for overall material substitution in Germany [42]; 1.2 tC/tC for timber in France [18]; 1.0 tC/tC for sawn wood in Finland [43], etc. However, as evidenced by fig.4b, the pertinent displacement factor values may be very different when definition (1) is applied at a definite moment or on average over a certain time horizon.…”
Section: Carbon Footprint Of Wood Utilisation As a Materialsmentioning
confidence: 99%
“…Secondly, when assessing the climate change mitigation potential of forest and wood use at a local, regional, national or global scale, a current practice is to apply "displacement factors" (DFs) to large segments of the HWP production [e.g. [18][19][20][21][22][23][24]. "Displacement factors" (or "substitution coefficients") are averaged differences between the absolute value | | of the carbon footprint of non-wood products and that | | of functionally equivalent wood products, normalised for convenience to the carbon mass content of the wood products [25]:…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, carbon storage should be taken as a negative value in the life cycle carbon emission of furniture, which can reduce the total carbon emission (Huang 2013). Geng et al (2019a) found that replacing non-wood materials with harvested wood products (HWP) can effectively reduce GHG. This means that the use of wood furniture can also bring some help, although in the construction industry, HWP is more effective in replacing greenhouse gas intensive materials in construction and furniture production.…”
Section: Introductionmentioning
confidence: 99%